2016
DOI: 10.1371/journal.pone.0162252
|View full text |Cite
|
Sign up to set email alerts
|

Mogrol Derived from Siraitia grosvenorii Mogrosides Suppresses 3T3-L1 Adipocyte Differentiation by Reducing cAMP-Response Element-Binding Protein Phosphorylation and Increasing AMP-Activated Protein Kinase Phosphorylation

Abstract: This study investigated the effects of mogrol, an aglycone of mogrosides from Siraitia grosvenorii, on adipogenesis in 3T3-L1 preadipocytes. Mogrol, but not mogrosides, suppressed triglyceride accumulation by affecting early (days 0–2) and late (days 4–8), but not middle (days 2–4), differentiation stages. At the late stage, mogrol increased AMP-activated protein kinase (AMPK) phosphorylation and reduced glycerol-3-phosphate dehydrogenase activity. At the early stage, mogrol promoted AMPK phosphorylation, inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…MII oocytes are predisposed to activation due to a decline in quality during postovulatory ageing. Therefore, we first examined whether MV can alleviate the activation of aged oocytes by assaying the effects of different doses of MV (25, 50 and 100 μM) based on our preliminary experiments and published reports [4, 15]. As shown in Figure 1A and 1B, cleaved and fragmented oocytes were regarded as activated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MII oocytes are predisposed to activation due to a decline in quality during postovulatory ageing. Therefore, we first examined whether MV can alleviate the activation of aged oocytes by assaying the effects of different doses of MV (25, 50 and 100 μM) based on our preliminary experiments and published reports [4, 15]. As shown in Figure 1A and 1B, cleaved and fragmented oocytes were regarded as activated.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that mogrosides have various biological activities, such as reducing blood glucose and lipid levels [13], as well as anti-diabetic [2], anti-inflammatory [14], anti-tumour and anti-carcinogenic effects [7, 11, 12]. In addition, several studies have reported that MV is a powerful antioxidant that scavenges free radicals [15]. Mogrosides, the primary component of which is MV, reduce oxidative stress in the livers of high-fat diet-induced obese mice and alloxan-induced diabetic mice [1618].…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine 5′‐monophosphate‐activated protein kinase is activated by natural products, such as ginsenoside (Yao et al, ), oleanolic acid (Nie et al, ) and ursolic acid (Meng et al, ), all of which suppress the release of inflammatory cytokines in LPS‐induced ALI. It has been demonstrated that mogroside V and its aglycone (mogrol) are both potent AMPK activators (Chen et al, ; Harada et al, ; Luo et al, ). In the present study, in vivo results demonstrated that LPS significantly down‐regulated the protein expression of p‐AMPK in the lungs compared to the control group, but MGIIIE treatment induced phosphorylation of AMPK in LPS‐induced ALI mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A group of cucurbitane‐type triterpenosides, called mogrosides, was extracted from S. grosvenorii and included mogroside IV, IVE, V and IIIE; siamenoside I; among others, and these mogrosides show various bioactivities, including anti‐tumour, antiinflammation, anti‐oxidative, anti‐obesity, anti‐diabetic, anti‐bacterial and anti‐allergic effects (Chen et al, ; Di et al, ; Jin and Lee, ; Sun et al, ). Previous studies have reported that mogroside V attenuates LPS‐induced ALI in mice (Shi et al, ), and the aglycone of mogrosides (mogrol) activates AMPK in hepatocytes and adipocytes (Harada et al, ; Luo et al, ). However, whether AMPK activation is involved in the protection of mogrosides against LPS‐induced ALI has not been clearly illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…[11,[13][14][15] Mogrol, a tetracyclic triterpenoids compound of Siraitia grosvenorii Swingle, could suppress leukemia cell growth via inhibition of the STAT3 and ERK1/2 pathways, induce K562 cell apoptosis by suppressing Bcl-2 expression, [16] activate AMP-activated protein kinase (AMPK) in the HepG2 cell line, [17] increase AMPK phosphorylation and reduce glycerol-3-phosphate dehydrogenase activity. [18] But no researches about the effects of mogrol on the inflammation and apoptosis were carried out in AD model induced by Ab 1-42 .…”
Section: Introductionmentioning
confidence: 99%